Pergulatan Aliran Kepercayaan dalam Panggung Politik Indonesia, 1950an-2010an: Romo Semono Sastrodihardjo dan Aliran Kapribaden - Aryono Aryono (Jurnal Sejarah Citra Lekha, 2018)
This article discusses about the efforts of creeds religion flourished to maintain their existence since the 1950s until the late 2010’s in Indonesia. Using historical method, this article found the interesting facts about the struggle of creeds religion in political stage of Indonesia. In 1953, for example, the Ministry of Religion Affairs noted that there were 360 groups protected by the government according on the Constitutional Law 1945 Article 29. After the tragedy of 1965, migration of members to the religions took place. When Soeharto became president, these groups was allowed to flourish. However, they got discrimination and always being watched. The new hope was arose in 2006, when the government issued Law No. 23/2006 about Population Administration, although it still requires to fill the religious column in national identity card (KTP). In the end 2017, the Constitutional Court issued a fatwa related to the status of religious column in KTP of the creeds religion. This condition also encompassed to Aliran Kapribaden’s Romo Semono Sastrodiharjo in Purworejo, Central Java. This discrimination must be terminated, in the name of unity in diversity.